Collision adenocarcinoma–carcinoid tumor of the rectum arising in ulcerative colitis. (2016) - Yamazaki, Nobuyoshi; Nishizawa, Yuji; Kojima, Motohiro; Sugano, Nobuhiro; Kobayashi, Akihiro; Ito, Masaaki; Saito, Norio
Abstract: A case of a collision carcinoma–carcinoid tumor of the rectum that arose in ulcerative colitis (UC). The patient was a 78-year-old man with a rectal tumor, who was diagnosed as having UC at 70 years of age. The tumor was diagnosed by endoscopy as a deep submucosal invasive rectal carcinoma. The patient underwent trans-anal local excision. Pathological examination of Hematoxylin–Eosin stained slides showed two different histological types: a conventional well differentiated tubular adenocarcinoma with submucosal invasion, and another that was composed of small cells with uniform nuclei and eosinophilic granular cytoplasm arranged in a trabecular pattern. Immnohistochemically, these cells were positive for chromogranin A and CD56. These cells exhibited a Ki-67 index that was less than 2% and mitosis in less than 1/10 HPF. These areas showed clear margins. Therefore, this tumor was considered to be a collision carcinoma–carcinoid tumor. Ultimately, the patient died 2 years after the local excision due to recurrence. Collision carcinoma–carcinoid tumors arising in ulcerative colitis are extremely rare. Collectively, it is considered that the behavior of the collision tumor is relatively aggressive. More careful surveillance of colorectal collision or composite carcinoma–carcinoid tumors is necessary, even when the carcinoma is early stage or the carcinoid is small.